RISIKO PERBANKAN DALAM PROFITABILITAS BANK PEMBANGUNAN DAERAH PERIODE 2018-2019 - Alifia Nur Haristi; Gusganda Suriamanda (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2021)
This research was aimed at Regional Development Banks listed on the Indonesia Stock Exchange for the period 2018-2019. This research was a quantitative research, with the selected sample of 19 banks for analysis with the ratio of credit risk (NPL), market risk (NIM), liquidity risk (LDR), operational risk (BOPO) to profitability (ROA). The research analysis technique in this research wass multiple linear regression analysis technique. The results showed that Net Interest Margin (NIM) had a significant positive effect, Operational Costs on Operating Income (BOPO) had a significant negative effect. Non-Performing Loans (NPL) and Loan to Deposit Ratio (LDR) have no effect on ROA, while simultaneously have a significant effect